Integrating Environmental Impact in Health Technology Assessment: An Exploratory Study - Ducrot, Coline; Péron, Julien; Delaye, Matthieu; Pérol, David; Durand-Zaleski, Isabelle; Piffoux, Max (PharmacoEconomics, 2025)
To what extent a care pathway, due to its associated pollution, may be more detrimental to future health than beneficial to contemporary patients is still an open question. We present a methodological framework to integrate pollutant-induced future health damages in health technology assessment (HTA) metrics like quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs) for a better evaluation of the cost effectiveness of care pathways. We used the ReCiPe model to estimate the future detrimental health impact (in disability-adjusted life years [DALY]) of pollutants from the US healthcare system, showing the major impact of GHG emissions compared with other pollutants. An adapted version of the ReCiPe model was used to convert GHG emissions from care pathways into future DALY , QALY , and life years (LY ), as well as the associated confidence intervals. For a given care pathway, future health damages were compared with patient benefits (e.g., QALY /QALY ). Damages may also be integrated in the ICER by subtracting future health losses from patient health benefits. Case applications are provided. Future damages to health emerging from pollutants emitted by the US healthcare system were estimated at 7,363,000 DALYs per year. Focusing on GHG emissions to estimate pollutant impact is reasonable, as they represent >90% of future damages. We provide estimates to convert GHG emissions into future health damages in DALY, QALY, or LY (and associated uncertainty), taking into account future impacts over different time horizons (20, 100, or 500-1000 years) and using different discount rates for future health impact (0 or 3%). We recommend estimating future damages using an egalitarian perspective (with a 0% discount rate) to maintain intergenerational equity. The QALY /QALY ratio allows weighting future detrimental effects of care pathways against their benefits. For health economic evaluations, we recommend integrating GHG emissions into the ICER, preferably in its denominator (QALY, DALY, LY). When focusing on specific care pathways, health gains may be substantially limited by future GHG-related detrimental impacts, especially for chronic treatments in low-risk populations. Some care pathways, like influenza vaccination, improve patient health while mitigating GHG. Accounting for GHG emissions may substantially favor or penalize one strategy over another in terms of ICER. Confidence intervals of the results were wide due to large uncertainties regarding long-term predictions. HTA should consider care pathways' impact on future health to better assess the impact and cost effectiveness of health technologies. Under the hypothesis of intergenerational equity, GHG accounting has a substantial impact, and may presumably impact the decisions of HTA bodies. It may also be seen as an ecological bonus/malus for care pathway developers and pharmaceutical companies, incentivizing the development of greener care pathways. None.